NOVEL PERSPECTIVES ON THE CONTRIBUTORS TO INFLAMMATORY BOWEL DISEASE DEVELOPMENT - KIANI, FA; FAROOQ, AA; JAVID, MA; SALEEM, MU; AHMED, Z; RASOOL, F; KHAN, S; NAWAZ, M; AZEEM, MS; MEHMOOD, K (Biological and Clinical Sciences Research Journal, 2024)
Irritable bowel disease (IBD), commonly referred to as Crohn's disease (CD) and ulcerative colitis (UC), is a persistent and recurring inflammation of the gastrointestinal tract (GIT). Despite the increasing prevalence of IBD globally, its precise aetiology remains unidentified, and no definitive treatment or cure has been established. The intricate interplay among environmental influences, genetics, and the host's immune system is believed to be the primary aetiology of IBD. Recent advancements in next-generation sequencing technologies indicate that IBD is linked to alterations in the function and composition of the gut microbiota, called dysbiosis. Experimental and clinical evidence suggests that dysbiosis plays a crucial part in the onset of IBD. Despite extensive investigations aimed at identifying new pathogenic factors related to IBD, encompassing environmental, genetic, microbial, and immune response elements, a comprehensive knowledge of IBD aetiology still needs to be identified as the treatment for IBD patients requires improved outcomes. A more profound comprehension of the disease's aetiology may yield distinctive insights applicable to developing therapeutic strategies for IBD. Recent research has markedly enhanced our understanding of the pathobiology of IBD, resulting in substantial progress in its diagnosis and treatment. We have emphasized current advancements and discoveries about emerging elements that contribute to disease pathogenesis, such as gut microbiota, which significantly influence the aetiology of IBD and may serve as prospective targets for innovative therapeutics in IBD patients.